2021
DOI: 10.1097/aog.0000000000004579
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Future Direction of Postpartum Hemorrhage Risk Assessment

Abstract: In the United States, postpartum hemorrhage is a leading preventable cause of maternal mortality and morbidity. To reduce morbidity from postpartum hemorrhage, risk assessment is an important starting point for informing decisions about risk management and hemorrhage prevention. Current perinatal care guidelines from the Joint Commission recommend that all patients undergo postpartum hemorrhage risk assessment at admission and after delivery. Three maternal health organizations—the California Maternal Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…Related studies show that maternal deaths due to postpartum hemorrhage account for 80% of the total number of maternal deaths, and the important cause of postpartum hemorrhage is uterine contraction weakness [ 2 ]. In recent years, with the continuous development of obstetric medical technology, although the mortality rate of maternal direct death from postpartum hemorrhage is decreasing year by year, postpartum hemorrhage is still the first cause of maternal death [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Related studies show that maternal deaths due to postpartum hemorrhage account for 80% of the total number of maternal deaths, and the important cause of postpartum hemorrhage is uterine contraction weakness [ 2 ]. In recent years, with the continuous development of obstetric medical technology, although the mortality rate of maternal direct death from postpartum hemorrhage is decreasing year by year, postpartum hemorrhage is still the first cause of maternal death [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…While risk factors are well-documented from descriptive studies (i.e. longer second stage labor, infant macrosomia, oxytocin administration during labor); an estimated 40% of PPH occurs during births without these commonly-noted risk factors [ 8 , 19 , 61 64 ] as assessed with available screening tools. A reason for this inaccuracy in risk assessment is due to the fact that PPH is a diagnosis only made after a high cumulative blood loss has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although recent research has shown that intrapartum factors are valuable in predicting OBH related severe morbidity and mortality, none of these validation studies have determined how a dynamic approach, with reassessment after admission and inclusion of intrapartum risk factors, may modify risk and, ultimately, clinical decision making. 13,14 We seek to assess our dynamic hemorrhage risk assessment tool, which was built to predict hemorrhage and transfusion using risk factors in the literature, reflected also in recommendations by the CMQCC, the Association of Women's Health, Obstetric and Neonatal Nurses (AWHONN), and the Safe Motherhood Initiative (Table 1). 4,6,7 We hypothesize that inclusion of intrapartum risk factors immediately prior to delivery (pre-delivery) increases the sensitivity of…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the context of this study, which demonstrates increased predictability of OBH-T in high-risk patients with inclusion of intrapartum factors, we recommend that further studies consider examining blood preparation recommendations for high hemorrhage risk patients using data that integrates intrapartum factors in risk assessment. 13 The first strength of this study is the population, which is highly racially and ethnically diverse, and in a safety-net hospital setting. Notably, previous validation studies have not examined this population and hospital setting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation